A brief contraction has complex effects on summation of twitch pairs in human adductor pollicis. Issue 4 (18th March 2020) - Smith, Ian C.; Adam, Helen; Herzog, Walter
Abstract : New Findings: What is the central question of this study? How do contraction‐induced reductions in twitch duration, without changes in twitch force, affect summation of twitch pairs into higher force contractions in skeletal muscle? What is the main finding and its importance? Abbreviating twitch duration with a brief contraction resulted in enhanced summation of fully fused twitch pairs, but impaired summation in partially fused twitch pairs even after accounting for the differences in relaxation of the first twitch. An inherent mechanism which enhances relaxation without sacrificing force generation in forceful contractions would benefit cyclic muscle activities, such as locomotion. Abstract: During electrically evoked contractions of skeletal muscle, the interplay between twitch duration and the time between electrical stimuli (inter‐pulse interval, IPI) determines how effectively twitch forces summate into high force contractions. A brief muscle contraction can impair summation by abbreviating twitch duration, though it is not clear if these impairments occur at all physiologically relevant IPI. This study was designed to test how a brief contraction affects summation of nominally isometric twitch pairs with IPIs lasting 10–5000 ms. Left adductor pollicis muscles of human participants ( n  = 9) were electrically activated using stimulus pairs applied both before (Pre) and after (Post) a 10 Hz, 1.0 s contraction. Force–time records were mathematically separated into Pulse 1 (single twitch) and Pulse 2 (summated twitch) components. The ratio of Pulse 2 peak force to Pulse 1 peak force was used as our measure of summation effectiveness. Consistent with the observed decline of Pulse 1 duration at Post relative to Pre (4.7 ± 0.6%; P  < 0.001; duration was defined as the time from stimulation to the time required for active force to decline by 50%), summation effectiveness was higher at Pre than at Post at IPIs of 100–333 ms. Summation effectiveness was not different between Pre and Post at IPIs of 50–83 ms or 500–5000 ms. Intriguingly, summation effectiveness was higher at Post than at Pre at IPIs of 10–25 ms. In summary, a brief contraction has complex effects on the relationship between inter‐pulse interval and summation effectiveness. Future experiments are needed to reveal the mechanisms behind this novel observation. Abstract :